Reclaiming the Reservation: The Geopolitics of Wisconsin Anishinaabe Resource Rights - Silvern, Steven E. (eScholarship, University of California, 2000)
INTRODUCTION At the center of many disputes among indigenous people and nation-states is the question of resource sovereignty. Control over and access to natural resources is critical to the economic, cultural, and political survival of indigenous peoples situated within the political boundaries of nation-states such as the United States and Canada. The power to define and command space or territory is fundamental to the ability of sovereigns, both indigenous and non-indigenous, to control access to natural resources and thus the use and development of these resources. Conflict between indigenous groups and nations-states is not only about different and often opposing cultural, economic, or biological visions of natural resource management and development, but also different understandings of who legitimately controls a particular space and territory. Struggles over resource use and claims of resource sovereignty are contests about locating political boundaries and delineating political jurisdictions. Because control over territory defines political sovereignty, the historical and contemporary efforts of the Wisconsin Anishinaabe to retain control over their reservation territories and to share control of off-reservation ceded territories may be understood as a geopolitical struggle to retain, protect, and expand Anishinaabe sovereignty. This struggle over territory and sovereignty has occurred in the face of persistent efforts by state government to diminish Anishinaabe territoriality and extend state territoriality to on-reservation space.